Bridging the gap: A sex-based examination of shot types and effectiveness in professional padel - Conde-Ripoll, R.; Martín-Miguel, I.; Bustamante-Sánchez, Á.; Llanos-García, M. B.; García-Sánchez, J. M.; Escudero-Tena, A. (International Journal of Sports Science & Coaching, 2025)
This study examines shot distribution and effectiveness in men's and women's professional padel. The variables sex, type of shot and effectiveness of 19,509 shots corresponding to 12 matches were analyzed through descriptive (frequency and percentage) and inferential analyses (Chi-square (?2), Cramer's V (Vc) or corrected standard residuals (CSR)). Results showed that in both sexes, the most executed shots are bandeja, backhand volley, forehand volley, forehand and backhand. Although most of the shots are continuous, many winners or forced error generators are made with the smash, forehand volley, backhand volley, bandeja (only women) and recovery smash (only men). Similarly, both male and female players demonstrate a propensity for unforced or forced errors when executing the bandeja, forehand volley, backhand volley, forehand, or backhand. Conversely, male playeres exhibit a higher rate of winners (men: 39.6%; women: 34.6%), while female players display a higher frequency of unforced errors (men: 39.3%; women: 43.9%), with no disparity noted in the proportion of forced errors (men: 21.1%; women: 21.5%). Particularly, male players tend to produce winners, generators of forced error, continuity shots, forced errors and unforced errors using a distinct typology of shots compared to female players, perhaps due to physical or anthropometric differences or differences in their style of play. In conclusion, this study highlights sex-based differences in professional padel technical-tactical actions occurrence and effectiveness.